A variation on split-cast mounting for complete denture construction - Nogueira, Sergio Sualdini [UNESP]; Russi, S.; Compagnoni, Marco Antonio [UNESP]; Mollo, F. D. (Mosby, Inc, 2004)
dThis article describes a variation of the split-cast mounting technique wherein the border of the definitive cast is wrapped with masking tape to form a container for the dental plaster normally used to affix the cast to the articulator. The entire inferior surface of the cast is coated with a thin film of petroleum jelly, and the cast is mounted in the articulator. After the dental plaster has set, the cast is retained by means of the masking tape. The cast is separated from the dental plaster simply by removing the masking tape.